2018
DOI: 10.1257/jep.32.2.115
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between Cognitive Ability and Risk Preference

Abstract: This paper will focus on the relationship between cognitive ability and decision-making under risk and uncertainty. Taken as a whole, this research indicates that cognitive ability is associated with risk-taking behavior in various contexts and life domains, including incentivized choices between lotteries in controlled environments, behavior in nonexperimental settings, and self-reported tendency to take risks. One pattern that emerges frequently in these studies is that cognitive ability tends to be positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
110
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(127 citation statements)
references
References 62 publications
14
110
3
Order By: Relevance
“…48 Risk and time preferences are also related to cognitive ability; however, the relationship is likely weaker. Higher cognitive ability is associated with more patient behavior (see for example Dohmen et al, 2018 andJagelka, 2018). The effect of cognitive skills on risk aversion is more controversial and there have been studies which found a positive, negative or no link (see Dohmen et al, 2018 for a recent summary of the literature).…”
Section: Are Economists' Preferences Psychologists' Personality Skills?mentioning
confidence: 99%
“…48 Risk and time preferences are also related to cognitive ability; however, the relationship is likely weaker. Higher cognitive ability is associated with more patient behavior (see for example Dohmen et al, 2018 andJagelka, 2018). The effect of cognitive skills on risk aversion is more controversial and there have been studies which found a positive, negative or no link (see Dohmen et al, 2018 for a recent summary of the literature).…”
Section: Are Economists' Preferences Psychologists' Personality Skills?mentioning
confidence: 99%
“…A novel paper in using hypothetical measures of risk aversion as well 4 For North America, it has been found that estimates from highquality stated-preference studies tend to be close to those from HWN studies (Robinson & Hammitt, 2016). 5 Risk preferences are typically elicited using observed real behaviors (e.g., smoking behavior, alcohol drinking status), survey measures of hypothetical behaviors (e.g., hypothetical gambles), or self-reported willingness to take risks (Dohmen, Falk, Huffman, & Sunde, 2018). as observed behaviors is Hammitt and Haninger (2010). Recent empirical developments in this line are scarce, although an ambiguous effect of health in the VSL has been found (Hammitt, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Risk preferences are typically elicited using observed real behaviors (e.g., smoking behavior, alcohol drinking status), survey measures of hypothetical behaviors (e.g., hypothetical gambles), or self‐reported willingness to take risks (Dohmen, Falk, Huffman, & Sunde, ).…”
mentioning
confidence: 99%
“…Frederick et al (2002) report a similarly wide range of individual discount rates in their survey. 14 There are studies (e.g Dohmen et al, 2010Dohmen et al, , 2018b. that document a positive relation between cognitive abilities and risk taking.…”
mentioning
confidence: 99%